If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3x+23=5x
We move all terms to the left:
3x+23-(5x)=0
We add all the numbers together, and all the variables
-2x+23=0
We move all terms containing x to the left, all other terms to the right
-2x=-23
x=-23/-2
x=11+1/2
| -3y-3=8y-36 | | 3x-1/10-4x+2/6=-1 | | -4+4(6k+3)=32 | | -46=-6u | | 28x-19=26x+5 | | x-4-4x=6x+8-8x | | 28x-18=26x+5 | | 3/7x+4=15 | | 39=y/3+11 | | 28x-14=26x+5 | | 8y+40+y=2y+5 | | -6(3r+6)=6=6 | | 8x+5x+6=-35.6 | | 3(v+3)-4=5 | | H=4+33t+-16t2 | | 4-(1-7x)^1/3=0 | | 3(-2x+4)=6(-x+2) | | -5t+2t+9=18 | | 78898t=78 | | -4(2x-6)=-8 | | 319=11x+1 | | 6(-5x+x)=108 | | 2f+3=11f-22 | | 2f+3=11f-23 | | 2f+5=11f-24 | | -59=-4x | | 2((x-3)=3x-4 | | -2v−3v=-10 | | -8(7-6x)=-8 | | 32-2n=4n | | -4=-16/g | | 6a+2a=21 |